PENGARUH BIAYA PRODUKSI DAN BIAYA PROMOSI TERHADAP PENJUALAN PT. ULTRAJAYA MILK INDUSTRY TBK. - Silva Anne Rupaida; Deden Edwar Yokeu Bernardin (Ekspansi: Jurnal Ekonomi, Keuangan, Perbankan, dan Akuntansi, 2016)
Abstract: The purpose of this research is to know the effect of production cost and promotion cost to sales at PT Ultrajaya Milk Industry Tbk which is registered at Indonesia Stock Exchange. Analysis method for this research are using descriptive quatitive. The population for this research using financial report from PT Ultrajaya Milk Industry. The sample for this research using financial report form PT Ultrajaya Milk Industry in last 7 years from years 2008 until 2014. This research adapting application program SPSS version 20 with adapting double regretion analysis. The result of double regretion analysis in this research shows that the connection partially between production cost and sales are affected significantly at 0,829 or 82,9%, and promotion cost not so affected to sales at 0,902 or 90,2%, then the rest at 0,098 or 9,8% which is another factor that doesn’t researched in this research. Keywords: Production Cost, Promotion Cost, Sales